Investigation of the Immunity to Voltage over Stress Requirement for the Electrical Seat Latch Actuator - (:unkn) unknown (IEEE, 2017)
The vehicle has foldable rear and front seat structure. The electrical seat latch for vehicle is a component which provides electrically release the seat from vehicle body rather than mechanical user interaction. In this study, electrical seat latch mechanisms and structures are investigated. Accarding to international standart and customer EMC (Electromagnetic Compability) requirements, the electrical seat latch component category types are searched. The electrical seat latch structures are evaluated in terms of EMC requirements and component category types. Resultly, the usage of reverse polarity protection and over voltage circuits are suggested for providing the immunity voltage to over stress requirement for electrical seat latch.
Keywords: component; electrical seat satch; actuator; reverse polarity protection; overvoltage protection; solenoid actuator